PENDAMPINGAN ADAPTASI KEBIASAAN BARU SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19 - Alda Bernika Ifada,; Alfina Rahma Dewi,; Kartika Nur Alfaeny,; Tazkiyah Eka Wulandari,; Tiara Puspa,; Wisudani Rahmaningtyas, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The determination of Covid-19 as a pandemic by WHO and its spread to various regions in Indonesia has made major changes in people's daily lives. As one of the preventive measures promoted by the government is to implement the Adaptation of New Habits, it is necessary to provide assistance to the community, including the people in the Pati area, which had experienced an increase in cases some time ago. The Adaptation of New Habits mentoring program was carried out in Soneyan Pati Village using the lecture method on the importance of applying health protocols in social life, double use of masks, and proper hand washing as one way that can be used to reduce the spread of the virus. As a result, the people of Soneyan Village have realized the importance of implementing Health protocols as an adaptation to new habits, and how to wash their hands properly.